Proactive Personality & Employee Creativity: The Role of Organizational Learning Culture as Mediator - Karina A. H. Putri; Arum Etikariena (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to determine the role of organizational learning culture on the relationship between proactive personality and employee creativity. The study uses a self-report online survey that was distributed to 158 employees in a company engaged in the construction and repair of network infrastructure in Indonesia. The data analysis technique used Hayes PROCESS Model 4 (Mediator Regression Analysis). The results of the research through the perspective of person-fit theory show that employees with a high level of proactive personality will have a high level of creativity, and will increase when employees are in an organizational learning culture. Organizational learning culture is considered to have a positive influence on employee creativity. Organizations need to consider implementation in increasing creativity through organizational learning culture.